2006
DOI: 10.1007/s10780-006-8399-8
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Framework for Contextual Science Teaching

Abstract: The contextual approach to teaching is generally recognized as a reasonable and desirable strategy to enhance student learning in science. Using several cognitive and learning theories together with various philosophical considerations, I identify five distinct contexts that are important in engaging learners: the theoretical, practical, social, historical, and affective. Based on these five contexts, I construct a model for teaching and learning, named the Story-Driven Contextual Approach (SDCA), in which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
28

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 41 publications
1
63
0
28
Order By: Relevance
“…However they showed that the learners hoped that the contexts would improve their learning. This is in agreement with proponents of the use of contexts in the learning of mathematics (Boaler, 1993b(Boaler, , 1994Klassen, 2006;Clarke & Helme, 1998). These advocates allude that contexts motivate and engage learners.…”
Section: Reasons For Preferring Core Contextssupporting
confidence: 86%
See 3 more Smart Citations
“…However they showed that the learners hoped that the contexts would improve their learning. This is in agreement with proponents of the use of contexts in the learning of mathematics (Boaler, 1993b(Boaler, , 1994Klassen, 2006;Clarke & Helme, 1998). These advocates allude that contexts motivate and engage learners.…”
Section: Reasons For Preferring Core Contextssupporting
confidence: 86%
“…Reasons for learning in contexts range from providing learners with a familiar allegory, to enhancing the transfer of mathematical learning through a demonstration of the connections between school mathematics and the real world (Boaler, 1993b(Boaler, , 1994 and motivating and engaging learners (Boaler, 1993a(Boaler, , 1994Klassen, 2006;Clarke & Helme, 1998). Contexts enable instructors to design a teaching sequence sensitive to learners' needs, give learners the chance to position their understanding in their own familiar knowledge and promote the reinvention of mathematics (Gravemeijer & Doorman, 1999).…”
Section: The Use Of Contexts In School Mathematicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The key to successful learning lies in the connectedness of the learned knowledge to what seems meaningful to the learner (Caine & Caine, 1991). Much research supports this type of learning and argues that it is significant for the learners (Klassen, 2006). Roth & Roychoudhury (1993) found a link between contextual learning and learner's motivation.…”
Section: Introductionmentioning
confidence: 99%